Case Report: Functional and Symptomatic Improvement With Cariprazine in Various Psychiatric Patients: A Case Series - Vannucchi, Tommaso; Taddeucci, Costanza; Tatini, Lorenzo (Frontiers in Psychiatry, 2022)
Cariprazine is a third-generation antipsychotic medication approved for the treatment of schizophrenia and bipolar disorder, with unique pharmacodynamic and pharmacokinetic properties. In this case series, the functional and symptomatic improvement of three patients is described who had been diagnosed with different psychiatric disorders and exhibited various symptoms from psychotic to mood symptoms. The first case is about a young male patient with bipolar disorder and cocaine abuse who managed to become abstinent with cariprazine. The second and third cases describe patients with psychosis suffering from positive, cognitive and mood symptoms who were non-adherent to previous medication. In both cases, cariprazine was well-tolerated and effective in alleviating symptoms, thus improving their everyday functioning as well. In the discussion, the associations between symptom domains and the receptor profile of cariprazine are also highlighted, providing an explanation to the observed effects. It is concluded that cariprazine is a good treatment option for patients with symptoms of psychosis and addiction; is well-tolerated without the induction of side effects such as weight gain or sedation; and is appropriate for patients who have problems with adherence.